Control of Natrium Oxide (NOX) and Carbon Oxide (CO) through Catalyst Hydro Carbon Coffee Leather Waste on the Motor Fuel - Dani Irawan; Mujahid Wahyu; Nila Nurlina (VANOS Journal of Mechanical Engineering Education, 2020)
The research objective was to determine the effect of using HCL solution and coffee bean husk on levels of (Sodium Oxide) Nox and Carbon Oxide (CO) . The method of this research is tru experiment on the process of carbon activation carried out by using HCl solution. The results showed that there was an effect of coffee beans and the use of HCL solutions on Nox and CO levels ( can reduce CO exhaust emissions in the range of 6.62-39.02% and reduce exhaust emissions of NOx in the range 13.08-39.05%)